situation in the old city - Hamza Ennab; Khaldon Halaweh; saed Herzallah; Ayed Adnan Salqan (My University, 2014)
The issue of water is considered to be a basic and vital component of the social, economical and political fabric of Palestine. Water represents the basic foundation for sovereignty and is the most important element needed to ensure actual independence. Water symbolizes the attachment of people to their land and is the key to all economical and social development. The Palestinian Authority realized the importance and necessity of devising strategic plans for the water sector. They are striving to improve the water situation in Palestine in order to ease the standard of living for their citizens through means of the Palestinian Water Authority and various organizations working in water.The water source in Palestine is composed of renewable groundwater, which is estimated at a capacity of 785 825 million cubic meters and streams in valleys estimated at 215 million cubic meters. In addition to that is the Jordan River whose annual discharge is estimated at 1320 million cubic meters upon its entrance to the Tabarya Lake. The quantity of water decreases to 115 million cubic meters as it reaches the Dead Sea. However, Palestinians are deprived from their water rights to this river, in accordance to international law, and are even forbidden from reaching it.The total annual Palestinian consumption of water for drinking in 2008 was approximately 94 million cubic meters, 54 million cubic meters of it was purchased from Israel (despite the fact that Palestinian consumption was measured at 101 million cubic meters in 2005, according to the PA).Despite the injustice, in 1993 the Oslo Accord determined that in reality the Palestinian consumption was estimated at 118 million cubic meters. 123 million cubic meters of water are used annually for irrigation (this amount was 172 million cubic meters in 2005, according to studies conducted by the PA). In Gaza, 169 million cubic meters of water are consumed annually from the coastal basin there for agricultural and residential use. This surpasses by far the renewable groundwater which feeds into the basin which is estimated at 55 million cubic meters annually. As a result this has caused the quality of water in the basin to decrease thus making it unfit for human consumption (according to current studies; only 10% of water extracted from the basin is fit for human use).ObjectivesThe main objective of this work is to understand the water situation in the old city by considering the supplied and the consumed water. And to analyze the existing water network through the estimate of water losses and try to find the reasons for it. Finally, the project will redesign the water network to be capable for the next 30 years.